Profiling of adulterated dietary supplements in Iraq using gas chromatography-mass spectrometry - Al-Sakini, Farah Faris Hayder (2023)
In Iraq, the usage of weight-loss medications has grown in popularity as more people look for an instant solution to their weight problems. Nevertheless, there are many adulterated slimming pills on the market that put users' health in danger. These tablets often contain hazardous additives like ephedrine, sibutramine, and phenolphthalein, which can have severe side effects like heart palpitations, convulsions, and even death. In order to address this alarming issue, adulterated 30 slimming pills are being profiled in Iraq using thin layer chromatography (TLC) and gas chromatography-mass spectrometry (GC-MS). The TLC technique is a quick, simple, and effective method for screening and analyzing mixture components. From the TLC spots which get from different 30 samples a clear spot for sibutramine Rf of (0.56 ±0.02) and caffeine also give clear spots in Rf of (0.71±0.02). The very sensitive analytical method known as GC-MS is capable of finding and identifying minute amounts of various chemical compounds including caffeine, sibutramine and phenolphthalein that were not listed as ingredients in the samples. in combinations. The research aims to profile slimming pills in Iraq using GC-MS to identify illegal drugs, ensuring the safety and efficacy of medication. The GC-MS was conducted for phenolphthalein, sibutramine and caffeine in total ion current of sibutramine retention time( 12.7±0.8) , phenolphthalein retention time (23.7±0.6) and caffeine retention time (13.4±0.3).So, The study aims to enhance regulatory policies for pills in Iraq, ensuring safety and efficacy. It will identify contaminants and unsafe ingredients in weight loss supplements and dietary supplements.